High-temperature-resistant heavy-duty anticorrosive fluorosilicone polymer coating as well as preparation method and application thereof

By using high-temperature heavy corrosion-resistant fluorosilicone polymer coating composed of fluorosilicone resin and nano-preservative materials, the problem of poor corrosion resistance in high-temperature environments is solved, and the efficient corrosion resistance and wear resistance of the coating is achieved.

CN119391300AActive Publication Date: 2025-02-07XIAN DEZAI ELECTRIC POWER TECH CO LTD

Patent Information

Application Number
CN202411703619.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-07
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Existing high-temperature anti-corrosion coatings have problems such as unstable coating quality, easy to fall off, poor anti-corrosion performance, and expensive prices, especially in high-temperature environments.

Method used

It is made of fluorosilicone resin, nano-anti-corrosion materials, wear-resistant powders, anti-rust pigments, silicone dispersants, polysiloxane defoaming agents, silicone-type leveling agents, polyamide wax-type anti-deposition additives High temperature-resistant heavy corrosion-resistant fluorosilicone polymer coating composed of amino curing agent and aminosilane coupling agent improves the adhesion, corrosion resistance and high temperature of the coating by modifying and synthesizing fluorosilicone resins and using nanomaterials. Anti-corrosion performance.

Benefits of technology

It has achieved significant improvement in the stability and corrosion resistance of the coating in high temperature environments, and has excellent wear resistance and chemical resistance, while reducing curing temperature and construction costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391300A_ABST
    Figure CN119391300A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of special coating materials, in particular to a high-temperature-resistant heavy-duty anticorrosive fluorosilicone polymer coating as well as a preparation method and application thereof. The high-temperature-resistant heavy-duty anticorrosive fluorosilicone polymer coating is prepared from the following components in parts by mass: 80-100 parts of fluorosilicone resin, 10-15 parts of a nano anticorrosive material, 5-15 parts of wear-resistant powder, 5-10 parts of an anti-rust pigment, 1-2 parts of a siloxane dispersant, 1-2 parts of a polysiloxane defoaming agent, 1-2 parts of an organic silicon leveling agent, 1-3 parts of a polyamide wax anti-settling aid and 25-35 parts of an amino curing agent. 2 to 5 parts of an amino silane coupling agent; and the fluorosilicone resin has the molecular weight of 8000-12000 and contains silicon oxygen bonds. The high-temperature-resistant heavy-duty anti-corrosion fluorosilicone polymer coating prepared by the invention improves the adhesive force to a substrate, can be cured at normal temperature, and has excellent high-temperature anti-corrosion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of special coating materials, and more specifically to a high-temperature resistant and heavy-duty corrosion-resistant fluorosilicone polymer coating, a preparation method thereof, and an application thereof. Background Art

[0002] The anti-corrosion problem of metal materials seriously affects the service life and safety of equipment. Especially for high-temperature equipment with application scenarios in the temperature range of 100℃ to 200℃, there is dual corrosion in the gas phase and liquid phase in the high and low temperature alternating environment. The existing anti-corrosion coatings have problems such as unstable coating quality, easy to fall off, poor anti-corrosion performance, and high price. It is necessary to develop a new type of anti-corrosion coating with superior performance.

[0003] High temperature resistant heavy duty anti-corrosion coatings usually refer to special functional coatings that can withstand high and low temperature alternation and corrosive environments for a long time, so that the protected objects maintain certain physical and chemical properties and can play their role normally in high temperature environments. The components of high temperature resistant heavy duty anti-corrosion coatings include high temperature resistant film-forming substances, pigments and fillers, solvents and additives. There are two main categories of existing organic high temperature resistant heavy duty anti-corrosion coatings: organic fluorine resin high temperature resistant coatings and organic silicone resin high temperature resistant coatings.

[0004] The side groups of organic fluorine resin are short and the structure is saturated, so it has excellent chemical resistance and chemical stability; organic fluorine resin is completely non-toxic and friendly to the environment and human health; the cohesive force of organic fluorine resin chain segments is large, which gives organic fluorine resin strong surface self-cleaning properties, but organic fluorine resin has poor wettability to pigments and fillers and poor solubility in organic solvents. At the same time, because organic fluorine resin contains fluorine, its cost is relatively high, which limits the promotion and application of organic fluorine resin.

[0005] The main chain of silicone resin is composed of Si-O chain segments, and the side chains are other various organic groups. Therefore, silicone resin has both organic and inorganic structures. The relative electronegativity of the two atoms in the Si-O bond is very different, so the polarity of the Si-O bond is large. Due to the above reasons, silicone resin has both organic and inorganic properties. Therefore, silicone resin has excellent weather resistance, heat resistance, acid rain resistance, stain resistance, light retention, moisture resistance, waterproofness, chemical stability and electrical insulation. However, it is precisely because of the high polarity of the Si-O bond of silicone resin that it is easy to break the Si-O bond under the attack of electrophilic reagents or nucleophilic reagents. Therefore, the film-forming property of silicone resin is poor, the curing temperature is high, and the curing temperature is 150℃~250℃. The adhesion to the substrate is poor, and its high temperature corrosion resistance is also poor. Summary of the invention

[0006] In view of the above problems, the present invention provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating and its preparation method and application, which improves the adhesion to the substrate, can be cured at room temperature, and has excellent high temperature corrosion resistance.

[0007] The first object of the present invention is to provide a high-temperature resistant and heavy-duty anti-corrosion fluorosilicone polymer coating, which is made of the following components in parts by mass: 80 to 100 parts of fluorosilicone resin, 10 to 15 parts of nano-anti-corrosion materials, 5 to 15 parts of wear-resistant powders, 5 to 10 parts of anti-rust pigments, 1 to 2 parts of siloxane dispersants, 1 to 2 parts of polysiloxane defoamers, 1 to 2 parts of organosilicon leveling agents, 1 to 3 parts of polyamide wax anti-settling aids, 25 to 35 parts of amino curing agents, and 2 to 5 parts of aminosilane coupling agents.

[0008] Fluorosilicone resin is a fluorosilicone resin with a molecular weight of 8000 to 12000 and containing silicon-oxygen bonds.

[0009] For example, fluorosilicone resin is 80 parts, 85 parts, 90 parts, 95 parts or 100 parts, etc.; nano anticorrosion material is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc.; wear-resistant powder is 5 parts, 7 parts, 9 parts, 11 parts, 13 parts or 15 parts, etc.; rust-proof pigment is 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.; siloxane dispersant is 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or 2 parts, etc.; polysiloxane defoamer is 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or 2 parts, etc.; silicone leveling agents are 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or 2 parts, etc.; polyamide wax anti-settling aids are 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts, etc.; amino curing agents are 25 parts, 27 parts, 29 parts, 31 parts, 33 parts or 35 parts, etc.; aminosilane coupling agents are 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, etc.; but are not limited to the listed values, other values ​​not listed within the above numerical range are also applicable.

[0010] In a preferred embodiment of the present invention, the preparation method of fluorosilicone resin comprises the following steps:

[0011] Under an inert atmosphere, trifluoropropylmethylcyclotrisiloxane is added to a hydrochloric acid solution, and a first ring-opening polymerization reaction occurs at 80°C to 100°C to obtain a trifluoropropylmethylchloroazane polymer; for example, the temperature of the first ring-opening polymerization reaction is 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, etc.; but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0012] In an inert atmosphere, a trifluoropropylmethylchloroazane polymer and a tetramethyltetravinylcyclotetrasiloxane are mixed and preheated and dehydrated at 80°C to 100°C, and then a catalyst and a neutralizing agent are added to cause a second ring-opening polymerization reaction at 150°C to -160°C to generate an interpenetrating network fluorosilicone resin, and then the temperature is reduced to 80°C to 90°C for heat preservation reaction, and then cooled to room temperature to prepare a fluorosilicone resin. For example, the temperature of preheating and dehydration is 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, etc.; the temperature of the second ring-opening polymerization reaction is 150°C, 152°C, 154°C, 156°C, 158°C or 160°C, etc., and the temperature of the heat preservation reaction is 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, etc.; but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0013] In a preferred embodiment of the present invention, the molar ratio of trifluoropropylmethylcyclotrisiloxane to hydrochloric acid solution is 100:2-3; the reaction time of the first ring-opening polymerization reaction is 1h-2h. For example, the molar ratio of trifluoropropylmethylcyclotrisiloxane to hydrochloric acid solution is 100:2, 100:2.2, 100:2.4, 100:2.6, 100:2.8 or 100:3, etc., and the reaction time of the first ring-opening polymerization reaction is 1h, 1.2h, 1.4h, 1.6h, 1.8h or 2.0h, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0014] In a preferred embodiment of the present invention, the molar ratio of trifluoropropylmethylchloroazane polymer to tetramethyltetravinylcyclotetrasiloxane is 2:1-1.5; the reaction time of the second ring-opening polymerization reaction is 2h-3h. For example, the molar ratio of trifluoropropylmethylchloroazane polymer to tetramethyltetravinylcyclotetrasiloxane is 2:1, 2:1.1, 2:1.2, 2:1.3, 2:1.4 or 2:1.5, etc.; but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0015] In a preferred embodiment of the present invention, the amount of the catalyst added is 0.3% to 0.4% of the total mass of the trifluoropropylmethylchloroazane polymer and the tetramethyltetravinylcyclotetrasiloxane; for example, the amount of the catalyst added is 0.3%, 0.32%, 0.34%, 0.36%, 0.38% or 0.4% of the total mass of the trifluoropropylmethylchloroazane polymer and the tetramethyltetravinylcyclotetrasiloxane, etc.; but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0016] In a preferred embodiment of the present invention, the amount of the neutralizer added is 0.5% to 0.6% of the total mass of the trifluoropropylmethylchloroazane polymer and the tetramethyltetravinylcyclotetrasiloxane. For example, the amount of the neutralizer added is 0.5%, 0.52%, 0.54%, 0.56%, 0.58% or 0.6% of the total mass of the trifluoropropylmethylchloroazane polymer and the tetramethyltetravinylcyclotetrasiloxane, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0017] In a preferred embodiment of the present invention, the catalyst is a manganese catalyst and the neutralizer is AMP95.

[0018] In a preferred embodiment of the present invention, the nano anti-corrosion material is one or more of nano aluminum oxide, nano iron oxide, nano magnesium oxide, nano titanium dioxide and nano silica gel. Typical but non-limiting examples of the combination include a combination of nano aluminum oxide and nano iron oxide, a combination of nano iron oxide and nano magnesium oxide, a combination of nano titanium dioxide and nano silica gel, etc.

[0019] The wear-resistant powder is one or more of silicon carbide, wollastonite, zirconium oxide, white corundum and glass powder. Typical but non-limiting examples of the combination include a combination of silicon carbide and wollastonite, a combination of wollastonite and zirconium oxide, a combination of zirconium oxide and white corundum, a combination of white corundum and glass powder, etc.

[0020] The anti-rust pigment is one or more of zinc phosphate, aluminum tripolyphosphate, mica powder and iron oxide. Typical but non-limiting examples of the combination include a combination of zinc phosphate and aluminum tripolyphosphate, a combination of aluminum tripolyphosphate and mica powder, a combination of mica powder and iron oxide, and the like.

[0021] The second object of the present invention is to provide a method for preparing the above-mentioned high temperature resistant heavy corrosion resistant fluorosilicone polymer coating, which is prepared according to the following steps:

[0022] Weigh the following components in parts by mass: 80 to 100 parts of fluorosilicone resin, 10 to 15 parts of nano-anticorrosive materials, 5 to 15 parts of wear-resistant powders, 5 to 10 parts of anti-rust pigments, 1 to 2 parts of siloxane dispersants, 1 to 2 parts of polysiloxane defoamers, 1 to 2 parts of organosilicon leveling agents, 1 to 3 parts of polyamide wax anti-settling aids, 25 to 35 parts of amino curing agents, and 2 to 5 parts of aminosilane coupling agents.

[0023] 1 / 3 to 1 / 2 of the fluorosilicone resin, the organosilicon leveling agent, the siloxane dispersant, the wear-resistant powder and the anti-rust pigment are mixed evenly, ground, and then the remaining fluorosilicone resin is added and mixed evenly to obtain a first mixture.

[0024] The remaining fluorosilicone resin, nano anti-corrosion material and polyamide wax anti-settling aid are mixed evenly to obtain a second mixture.

[0025] After the first mixture and the second mixture are mixed, a polysiloxane defoamer is added. During spraying, an amino curing agent and an aminosilane coupling agent mixture are added and stirred evenly to obtain a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating.

[0026] The third object of the present invention is to provide the use of the above-mentioned high temperature resistant heavy corrosion resistant fluorosilicone polymer coating in the preparation of anticorrosion materials, comprising the following steps:

[0027] After the substrate is degreased and derusted, the high-temperature resistant and heavy-duty anti-corrosion fluorosilicone polymer coating is sprayed on the surface of the substrate, the total wet film thickness of the coating is controlled to be 1mm to 2mm, and the total dry film thickness of the coating is 0.5mm to 1mm. After spraying, it is dried at room temperature for 7 to 15 days to prepare a high-temperature resistant and heavy-duty anti-corrosion fluorosilicone polymer coating.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention selects a high molecular weight fluorosilicone resin with a molecular weight of 8000 to 12000 as a film-forming substance, which has a high adhesion to the substrate. The advantage of the silicon-oxygen bond on the fluorosilicone resin is that the bond energy strength is high, which can improve the corrosion resistance, high temperature resistance and wear resistance of the fluorosilicone resin. The addition of nano-anticorrosion materials improves the shielding effect of the coating and shields the penetration of corrosive media; anti-rust pigments are added as anti-corrosion components, which are used as inert materials to improve the chemical resistance of the coating; amino curing agents and silane coupling agents are added as curing agents. The amino curing agent, as the main curing agent component, undergoes a cross-linking reaction with the silicon-oxygen bonds of the fluorosilicone resin, and is matched with a silane coupling agent. The silane coupling agent can be self-cross-linked and can be dried and cured at room temperature, thereby improving the overall drying speed and performance indicators. In addition, it is also beneficial to improve the overall density and tensile strength of the coating, so that the coating has excellent corrosion resistance; the nano-anticorrosion material forms an interpenetrating network arrangement with the high molecular weight fluorosilicone resin in the coating, which plays an excellent shielding effect. Under the synergistic effect of all components in a reasonable ratio, it is ensured that the coating has heavy anti-corrosion performance. In addition, fluorosilicone polymer coatings have the advantages of low surface tension and self-cleaning properties of organic fluorine coatings, which makes it difficult for dust, salt, moisture, chemicals and other corrosive substances to adhere to the coating surface, greatly enhancing the high-temperature anti-corrosion performance.

[0030] (2) The polymer organic fluorine resin and silicone resin used in the present invention both have excellent high temperature resistance and can maintain toughness in a high temperature environment of 300°C for a long time. After the organic fluorine resin and silicone resin are modified to synthesize fluorosilicone resin, they have the advantages of good solubility and dispersibility of silicone resin, thereby improving the solubility of organic fluorine resin. The polymer fluorosilicone resin improves the disadvantage of low adhesion of silicone resin on the surface of the substrate when used alone, and can still maintain good thermal shock resistance in a high and low temperature alternating environment, thereby improving the overall adhesion and bonding strength.

[0031] (3) The present invention improves the wear resistance and erosion resistance of the fluorosilicone polymer coating by adding wear-resistant powders such as silicon carbide, wollastonite, zirconium oxide, white corundum, and glass powder, and adds a silane coupling agent to improve the crosslinking density and coating hardness, so that the coating has excellent wear resistance and erosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The schematic diagram of the preparation of trifluoropropylmethylsilyl chloride polymer according to the present invention is shown in FIG.

[0033] Figure 2 Schematic diagram of the preparation of fluorosilicone resin according to the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The invention provides a high-temperature resistant and heavy-duty anti-corrosion fluorosilicone polymer coating, which is prepared from the following components in parts by mass: 80 to 100 parts of fluorosilicone resin, 10 to 15 parts of nano anti-corrosion materials, 5 to 15 parts of wear-resistant powders, 5 to 10 parts of anti-rust pigments, 1 to 2 parts of siloxane dispersants, 1 to 2 parts of polysiloxane defoamers, 1 to 2 parts of organosilicon leveling agents, 1 to 3 parts of polyamide wax anti-settling aids, 25 to 35 parts of amino curing agents, and 2 to 5 parts of aminosilane coupling agents.

[0036] Fluorosilicone resin is a fluorosilicone resin with a molecular weight of 8000 to 12000 and containing silicon-oxygen bonds.

[0037] The present invention adopts a high-molecular fluororesin monomer and a high-molecular silicone resin monomer to be synthesized by a high-temperature chelating reaction in a certain proportion for optimization and modification, the synthesized fluorosilicone resin is used as the main film-forming substance, an amino curing agent is used as a curing agent to improve the drying speed and coating strength, a silane coupling agent is added to improve the crosslinking degree and toughness, and nano-anticorrosive materials, wear-resistant powders and functional anti-rust pigments are added to make the coating have excellent corrosion resistance and wear resistance; the coating has high hardness, strong flexibility, a low water vapor permeability coefficient and high flexibility, and can prevent the penetration of corrosive substances and long-term contact aging; at the same time, it has excellent wear resistance and avoids scouring and wear of corrosive substances. After the organic fluorine resin and organic silicone resin are modified to synthesize fluorosilicone resin, it has the advantage of good adhesion of organic fluorine resin, improves the adhesion of silicone resin, improves the poor wettability and solubility of organic fluorine resin coatings and the poor adhesion and general corrosion resistance of silicone resin coatings, improves the overall adhesion, heat resistance, corrosion resistance and wear resistance of the coating, and can be combined with a curing agent for room temperature heat curing. Specifically, the amino curing agent undergoes a substitution cross-linking reaction with the fluorosilicone resin, and the self-cross-linking properties of the silane coupling agent allow it to be dried and cured at room temperature, eliminating the high-temperature baking and curing molding conditions of traditional organic fluorine resin coatings and silicone coatings, and has made breakthrough progress in improving construction efficiency and reducing construction costs during the coating application process.

[0038] Furthermore, the preparation method of the fluorosilicone resin comprises the following steps:

[0039] In an inert atmosphere, trifluoropropylmethylcyclotrisiloxane is added to a hydrochloric acid solution, and a first ring-opening polymerization reaction occurs at 80°C to 100°C to obtain a trifluoropropylmethylchloroazane polymer; specifically, under the action of the hydrochloric acid solution, the silicon-oxygen bond of trifluoropropylmethylcyclotrisiloxane is ring-opened and chain-broken, a polycondensation reaction is performed, and a chloride ion undergoes a substitution reaction to generate a trifluoropropylmethylchloroazane polymer, such as Figure 1 shown.

[0040] In an inert atmosphere, a trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are mixed and preheated at 80°C to 100°C for dehydration, and then a catalyst and a neutralizing agent are added to cause a second ring-opening polymerization reaction at 150°C to 160°C to generate an interpenetrating network fluorosilicone resin, and then the temperature is lowered to 80°C to 90°C for heat preservation and reaction, and then cooled to room temperature to prepare a fluorosilicone resin. After the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are mixed and dehydrated, a catalyst and a neutralizing agent are added to break the internal silicon-oxygen bond of the tetramethyltetravinylcyclotetrasiloxane, and a substitution reaction is carried out with the chloromethyl group in the trifluoropropylmethylchloroazane polymer, and a macromolecular polycondensation reaction is completed to generate a fluorosilicone resin, such as Figure 2 shown.

[0041] Furthermore, the molar ratio of trifluoropropylmethylcyclotrisiloxane to the hydrochloric acid solution is 100:2-3; and the reaction time of the first ring-opening polymerization reaction is 1h-2h.

[0042] Furthermore, the molar ratio of the trifluoropropylmethylchloroazane polymer to tetramethyltetravinylcyclotetrasiloxane is 2:1-1.5; and the reaction time of the second ring-opening polymerization reaction is 2h-3h.

[0043] Furthermore, the added amount of the catalyst is 0.3% to 0.4% of the total mass of the trifluoropropylmethylchloroazane polymer and the tetramethyltetravinylcyclotetrasiloxane.

[0044] The added amount of the neutralizer is 0.5% to 0.6% of the total mass of the trifluoropropylmethylchloroazane polymer and the tetramethyltetravinylcyclotetrasiloxane.

[0045] Furthermore, the catalyst is a manganese catalyst.

[0046] The neutralizer is AMP95.

[0047] Furthermore, the nano anti-corrosion material is one or more of nano alumina, nano iron oxide, nano magnesium oxide, nano titanium dioxide and nano silica gel.

[0048] The wear-resistant powder is one or more of silicon carbide, wollastonite, zirconium oxide, white corundum and glass powder.

[0049] The anti-rust pigment is one or more of zinc phosphate, aluminum tripolyphosphate, mica powder and iron oxide pigment.

[0050] The present invention also provides a method for preparing the above-mentioned high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is prepared according to the following steps:

[0051] Weigh the following components in parts by mass: 80 to 100 parts of fluorosilicone resin, 10 to 15 parts of nano-anticorrosive materials, 5 to 15 parts of wear-resistant powders, 5 to 10 parts of anti-rust pigments, 1 to 2 parts of siloxane dispersants, 1 to 2 parts of polysiloxane defoamers, 1 to 2 parts of organosilicon leveling agents, 1 to 3 parts of polyamide wax anti-settling aids, 25 to 35 parts of amino curing agents, and 2 to 5 parts of aminosilane coupling agents.

[0052] 1 / 3 to 1 / 2 of the fluorosilicone resin, the organosilicon leveling agent, the siloxane dispersant, the wear-resistant powder and the anti-rust pigment are mixed evenly, ground, and then the remaining fluorosilicone resin is added and mixed evenly to obtain a first mixture.

[0053] The remaining fluorosilicone resin, nano anti-corrosion material and polyamide wax anti-settling aid are mixed evenly to obtain a second mixture.

[0054] After the first mixture and the second mixture are mixed, a polysiloxane defoamer is added and stirred evenly to obtain component A.

[0055] The amino curing agent and the aminosilane coupling agent are mixed to obtain component B.

[0056] During spraying, component A and component B are stirred evenly to obtain a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating.

[0057] The high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating prepared by the present invention can be used for high temperature, corrosion and wear of metal substrates, such as carbon steel, stainless steel, alloy steel, etc. The high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating prepared by the present application is used in the following steps:

[0058] (1) The substrate is degreased and derusted to at least Sa2.0 level; the construction environment is controlled at a temperature of 10°C to 35°C and a relative humidity of <90%.

[0059] (2) Use spraying method to spray the paint film to the specified thickness in multiple times. After each layer of coating is sprayed and dried, the next layer of spraying can be carried out.

[0060] (3) The total wet film thickness of the coating is controlled to be 1 mm to 2 mm, and the total dry film thickness of the coating is controlled to be 0.5 mm to 1 mm. After spraying, the coating is dried at room temperature for 7 to 15 days to prepare a high-temperature resistant and heavy-duty anti-corrosion fluorosilicone polymer coating on the surface of the substrate.

[0061] The siloxane dispersant used in the present invention is TSI-316. The polysiloxane defoamer is Deqian 5100 solvent-based defoamer. The organosilicon leveling agent is BYK-300. The polyamide wax anti-settling aid is PA-8610. The manganese catalyst is manganese acetate.

[0062] Example 1

[0063] This embodiment provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0064] Component A: 100 parts of fluorosilicone resin, 15 parts of nano anti-corrosion materials, 12 parts of wear-resistant powder, 6 parts of anti-rust pigment, 2 parts of siloxane dispersant, 1 part of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0065] Component B: 30 parts of 4-4'-dicyclohexylamine and 5 parts of aminosilane coupling agent.

[0066] The molecular weight of the fluorosilicone resin used in this embodiment is about 9,000.

[0067] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0068] The nano anti-corrosion material is a mixture of nano aluminum oxide and nano iron oxide in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0069] The wear-resistant powder is a mixture of wollastonite and zirconium oxide in a mass ratio of 1:2.

[0070] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and mica powder in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0071] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.

[0072] The preparation method of fluorosilicone resin comprises the following steps:

[0073] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 2 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 4000.

[0074] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 minutes under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted at 150° C. under argon protection for 2 hours to generate a macromolecular interpenetrating network fluorosilicone resin by ring-opening polymerization, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 hours, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin, and the molecular weight of the fluorosilicone resin is about 9000.

[0075] This embodiment also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0076] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0077] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0078] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0079] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0080] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0081] (6) During spraying, mix component A and component B evenly before use.

[0082] Example 2

[0083] This embodiment provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0084] Component A: 90 parts of fluorosilicone resin, 10 parts of nano anti-corrosion materials, 10 parts of wear-resistant powders, 6 parts of anti-rust pigments, 1 part of siloxane dispersants, 1 part of polysiloxane defoamers, 1 part of organosilicon leveling agents, and 1 part of polyamide wax anti-settling aids.

[0085] Component B: 35 parts of 4-4'-dicyclohexylamine and 5 parts of aminosilane coupling agent.

[0086] The molecular weight of the fluorosilicone resin in this embodiment is about 9,000.

[0087] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0088] The nano anti-corrosion material is a mixture of nano aluminum oxide and nano iron oxide in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0089] The wear-resistant powder is a mixture of wollastonite and zirconium oxide in a mass ratio of 1:2.

[0090] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and mica powder in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0091] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.

[0092] The preparation method of fluorosilicone resin comprises the following steps:

[0093] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 2 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 4000.

[0094] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 minutes under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted for 2 hours under argon protection at 150° C. to generate a macromolecular interpenetrating network fluorosilicone resin by ring-opening polymerization, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 hours, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin, and the molecular weight of the fluorosilicone resin is about 9000.

[0095] This embodiment also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0096] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0097] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0098] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0099] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0100] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0101] (6) During spraying, mix component A and component B evenly before use.

[0102] Example 3

[0103] This embodiment provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0104] Component A: 100 parts of fluorosilicone resin, 15 parts of nano anti-corrosion materials, 12 parts of wear-resistant powder, 6 parts of anti-rust pigment, 2 parts of siloxane dispersant, 1 part of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0105] Component B: 30 parts of 4-4'-dicyclohexylamine and 5 parts of silane coupling agent, that is, 35 parts of component B in total.

[0106] The molecular weight of the fluorosilicone resin in this embodiment is about 9,000.

[0107] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0108] The nano anti-corrosion material is nano titanium dioxide with a particle size of 5-10nm.

[0109] The wear-resistant powder is silicon carbide.

[0110] The anti-rust pigment is mica powder with a particle size of 5-10μm.

[0111] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.

[0112] The preparation method of fluorosilicone resin comprises the following steps:

[0113] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 2 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 4000.

[0114] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 minutes under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted for 2 hours under argon protection at 150° C. to generate a macromolecular interpenetrating network fluorosilicone resin by ring-opening polymerization, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 hours, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin, and the molecular weight of the fluorosilicone resin is about 9000.

[0115] This embodiment also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0116] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and a functional anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0117] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0118] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0119] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0120] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0121] (6) During spraying, mix component A and component B evenly before use.

[0122] Example 4

[0123] This embodiment provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0124] Component A: 100 parts of fluorosilicone resin, 10 parts of nano anti-corrosion materials, 15 parts of wear-resistant powder, 8 parts of anti-rust pigment, 2 parts of siloxane dispersant, 1 part of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0125] Component B: 35 parts of 4-4'-dicyclohexylamine and 5 parts of aminosilane coupling agent.

[0126] The molecular weight of the high molecular weight fluorosilicone resin in the coating is about 9000.

[0127] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0128] The nano anti-corrosion material is a mixture of nano aluminum oxide and nano iron oxide in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0129] The wear-resistant powder is a mixture of wollastonite and zirconium oxide in a mass ratio of 1:2.

[0130] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and mica powder in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0131] The aminosilane coupling agent is N-(β-aminoethyl-γ-aminopropyl)methylsilane.

[0132] The preparation method of fluorosilicone resin comprises the following steps:

[0133] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 2 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 4000.

[0134] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 minutes under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted for 2 hours under argon protection at 150° C. to generate a macromolecular interpenetrating network fluorosilicone resin by ring-opening polymerization, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 hours, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin with a molecular weight of about 9000.

[0135] This embodiment also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0136] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and a functional anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0137] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0138] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0139] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0140] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0141] (6) During spraying, mix component A and component B evenly before use.

[0142] Example 5

[0143] This embodiment provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0144] Component A: 100 parts of fluorosilicone resin, 15 parts of nano anti-corrosion materials, 12 parts of wear-resistant powder, 6 parts of anti-rust pigment, 2 parts of siloxane dispersant, 1 part of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0145] Component B: 30 parts of 4-4'-dicyclohexylamine and 5 parts of aminosilane coupling agent.

[0146] The molecular weight of the fluorosilicone resin used in this embodiment is about 8,000.

[0147] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0148] The nano anti-corrosion material is a mixture of nano aluminum oxide and nano iron oxide in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0149] The wear-resistant powder is a mixture of wollastonite and zirconium oxide in a mass ratio of 1:2.

[0150] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and mica powder in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0151] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.

[0152] The preparation method of fluorosilicone resin comprises the following steps:

[0153] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2.5, and heated to 80° C. under argon protection for 1 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 3000.

[0154] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 min under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted at 150° C. under argon protection for 2 h, and a ring-opening polymerization reaction occurs to generate a macromolecular interpenetrating network fluorosilicone resin, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 1 h, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin, and the molecular weight of the fluorosilicone resin is about 8000.

[0155] This embodiment also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0156] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0157] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0158] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0159] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0160] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0161] (6) During spraying, mix component A and component B evenly before use.

[0162] Example 6

[0163] This embodiment provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0164] Component A: 100 parts of fluorosilicone resin, 15 parts of nano anti-corrosion materials, 12 parts of wear-resistant powder, 6 parts of anti-rust pigment, 2 parts of siloxane dispersant, 1 part of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0165] Component B: 30 parts of 4-4'-dicyclohexylamine and 5 parts of aminosilane coupling agent.

[0166] The molecular weight of the fluorosilicone resin used in this embodiment is about 12,000.

[0167] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0168] The nano anti-corrosion material is a mixture of nano aluminum oxide and nano iron oxide in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0169] The wear-resistant powder is a mixture of wollastonite and zirconium oxide in a mass ratio of 1:2.

[0170] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and mica powder in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0171] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.

[0172] The preparation method of fluorosilicone resin comprises the following steps:

[0173] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:3, and heated to 80° C. under argon protection for 1.5 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 4000.

[0174] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1.5, and gradually heated to 100° C. for preheating and dehydration for 30 min under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted at 160° C. under argon protection for 3 h, and a ring-opening polymerization reaction occurs to generate a macromolecular interpenetrating network fluorosilicone resin, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 1.5 h, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin, and the molecular weight of the fluorosilicone resin is about 12,000.

[0175] This embodiment also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0176] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0177] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0178] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0179] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0180] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0181] (6) During spraying, mix component A and component B evenly before use.

[0182] Example 7

[0183] This embodiment provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0184] Component A: 80 parts of fluorosilicone resin, 12 parts of nano anti-corrosion materials, 5 parts of wear-resistant powder, 5 parts of anti-rust pigment, 1 part of siloxane dispersant, 2 parts of polysiloxane defoaming agent, 1.5 parts of organosilicon leveling agent, 3 parts of polyamide wax anti-settling aid.

[0185] Component B: 25 parts of 4-4'-dicyclohexylamine and 2 parts of aminosilane coupling agent.

[0186] The molecular weight of the fluorosilicone resin used in this embodiment is about 10,000.

[0187] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0188] The nano anti-corrosion material is a mixture of nano magnesium oxide and nano silica gel in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0189] The wear-resistant powder is a mixture of white corundum and glass powder in a mass ratio of 1:2.

[0190] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and iron oxide pigment in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0191] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.

[0192] The preparation method of fluorosilicone resin comprises the following steps:

[0193] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 3 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 5000.

[0194] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 minutes under argon protection. Then, a manganese catalyst of 0.4% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.6% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted at 150° C. under argon protection for 2 hours to generate a macromolecular interpenetrating network fluorosilicone resin by ring-opening polymerization, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 hours, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin, wherein the molecular weight of the fluorosilicone resin is about 10,000.

[0195] This embodiment also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0196] (1) 2 / 5 of high molecular weight fluorosilicone resin, silicone leveling agent and siloxane dispersant are mixed evenly, and wear-resistant powder and anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0197] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0198] (3) The remaining 3 / 5 of the high molecular weight fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0199] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0200] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0201] (6) During spraying, mix component A and component B evenly before use.

[0202] Example 8

[0203] This embodiment provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0204] Component A: 90 parts of fluorosilicone resin, 11 parts of nano anticorrosive material, 10 parts of wear-resistant powder, 10 parts of anti-rust pigment, 1.5 parts of siloxane dispersant, 1.5 parts of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0205] Component B: 30 parts of 4-4'-dicyclohexylamine and 4 parts of aminosilane coupling agent.

[0206] The molecular weight of the fluorosilicone resin used in this embodiment is about 10,000.

[0207] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0208] The nano anti-corrosion material is a mixture of nano magnesium oxide and nano silica gel in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0209] The wear-resistant powder is a mixture of white corundum and glass powder in a mass ratio of 1:2.

[0210] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and iron oxide pigment in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0211] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.

[0212] The preparation method of fluorosilicone resin comprises the following steps:

[0213] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 3 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 4000.

[0214] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 minutes under argon protection. Then, a manganese catalyst of 0.35% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.55% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted at 150° C. for 2 hours under argon protection to generate a macromolecular interpenetrating network fluorosilicone resin by ring-opening polymerization, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 hours, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin, wherein the molecular weight of the fluorosilicone resin is about 10,000.

[0215] This embodiment also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0216] (1) 1 / 2 polymer fluorosilicone resin, silicone leveling agent and siloxane dispersant are mixed evenly, and wear-resistant powder and anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0217] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0218] (3) The remaining 1 / 2 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0219] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0220] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0221] (6) During spraying, mix component A and component B evenly before use.

[0222] Comparative Example 1

[0223] This comparative example provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is basically the same as Example 1, except that the molecular weight of the fluorosilicone resin synthesized in this comparative example is 5000.

[0224] Component A: 100 parts of fluorosilicone resin, 15 parts of nano anti-corrosion materials, 12 parts of wear-resistant powder, 6 parts of anti-rust pigment, 2 parts of siloxane dispersant, 1 part of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0225] Component B: 30 parts of 4-4'-dicyclohexylamine and 5 parts of aminosilane coupling agent.

[0226] The molecular weight of the fluorosilicone resin used in this comparative example is about 5,000.

[0227] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0228] The nano anti-corrosion material is a mixture of nano aluminum oxide and nano iron oxide in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0229] The wear-resistant powder is a mixture of wollastonite and zirconium oxide in a mass ratio of 1:2.

[0230] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and mica powder in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0231] The silane coupling agent is 3-aminopropyltrimethoxysilane.

[0232] The preparation method of aminofluorosilicone resin comprises the following steps:

[0233] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 30 min to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 2000.

[0234] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 min under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted at 150° C. for 1 h under argon protection to generate a macromolecular interpenetrating network fluorosilicone resin, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 h, and the mixture is cooled to room temperature to prepare a stable macromolecular fluorosilicone resin with a molecular weight of about 5000.

[0235] This comparative example also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0236] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and a functional anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0237] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0238] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0239] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0240] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0241] (6) During spraying, mix component A and component B evenly before use.

[0242] Comparative Example 2

[0243] This comparative example provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is basically the same as Example 1, except that the molecular weight of the fluorosilicone resin synthesized in this comparative example is 20,000.

[0244] Component A: 100 parts of fluorosilicone resin, 15 parts of nano anti-corrosion materials, 12 parts of wear-resistant powder, 6 parts of anti-rust pigment, 2 parts of siloxane dispersant, 1 part of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0245] Component B: 30 parts of 4-4'-dicyclohexylamine and 5 parts of aminosilane coupling agent.

[0246] The molecular weight of the fluorosilicone resin used in this comparative example is about 20,000.

[0247] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0248] The nano anti-corrosion material is a mixture of nano aluminum oxide and nano iron oxide in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0249] The wear-resistant powder is a mixture of wollastonite and zirconium oxide in a mass ratio of 1:2.

[0250] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and mica powder in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0251] The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.

[0252] The preparation method of fluorosilicone resin comprises the following steps:

[0253] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 2 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 9000.

[0254] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 minutes under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted for 4 hours at 150° C. under argon protection, and a ring-opening polymerization reaction occurs to generate a macromolecular interpenetrating network fluorosilicone resin, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 hours, and the mixture is cooled to room temperature to prepare a stable polymer fluorosilicone resin with a molecular weight of about 20,000.

[0255] This comparative example also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0256] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and a functional anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0257] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0258] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0259] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0260] (5) Mix 4-4'-dicyclohexylamine and an aminosilane coupling agent to obtain component B.

[0261] (6) During spraying, mix component A and component B evenly before use.

[0262] Comparative Example 3

[0263] This comparative example provides a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, which is composed of the following components in parts by weight:

[0264] Component A: 100 parts of fluorosilicone resin, 15 parts of nano anti-corrosion materials, 12 parts of wear-resistant powder, 6 parts of anti-rust pigment, 2 parts of siloxane dispersant, 1 part of polysiloxane defoaming agent, 2 parts of organosilicon leveling agent, 2 parts of polyamide wax anti-settling aid.

[0265] Component B: 30 parts of 4-4'-dicyclohexylamine.

[0266] The molecular weight of the fluorosilicone resin used in this embodiment is about 9,000.

[0267] The molecular weight of 4-4'-dicyclohexylamine is about 1000.

[0268] The nano anti-corrosion material is a mixture of nano aluminum oxide and nano iron oxide in a mass ratio of 1:1, and the particle size of the nano anti-corrosion material is 5-10nm.

[0269] The wear-resistant powder is a mixture of wollastonite and zirconium oxide in a mass ratio of 1:2.

[0270] The anti-rust pigment is a mixture of zinc phosphate, aluminum tripolyphosphate and mica powder in a mass ratio of 1:1:1, and the particle size of the anti-rust pigment is 5-10 μm.

[0271] The preparation method of fluorosilicone resin comprises the following steps:

[0272] (1) Trifluoropropylmethylcyclotrisiloxane monomer and hydrochloric acid solution with a mass concentration of 5% were weighed according to a molar ratio of trifluoropropylmethylcyclotrisiloxane monomer to hydrochloric acid of 100:2, and heated to 80° C. under argon protection for 2 h to obtain a trifluoropropylmethylchlorosilane polymer with a molecular weight of about 4000.

[0273] (2) The trifluoropropylmethylchlorosilane polymer and tetramethyltetravinylcyclotetrasiloxane obtained in step (1) are mixed uniformly in a molar ratio of 2:1, and gradually heated to 100° C. for preheating and dehydration for 30 minutes under argon protection. Then, a manganese catalyst of 0.3% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane and a neutralizer AMP95 of 0.5% of the total mass of the trifluoropropylmethylchloroazane polymer and tetramethyltetravinylcyclotetrasiloxane are added, and the mixture is reacted at 150° C. under argon protection for 2 hours to generate a macromolecular interpenetrating network fluorosilicone resin by ring-opening polymerization, and then the reaction temperature is reduced to 80° C., the reaction is kept warm for 2 hours, and the mixture is cooled to room temperature to prepare a stable high molecular fluorosilicone resin, and the molecular weight of the fluorosilicone resin is about 9000.

[0274] This comparative example also provides a method for preparing a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, comprising the following steps:

[0275] (1) 1 / 3 of a high molecular weight fluorosilicone resin, an organosilicon leveling agent, and a siloxane dispersant are uniformly mixed, and wear-resistant powder and anti-rust pigment are added and stirred for 20 minutes to obtain a slurry.

[0276] (2) Grinding the slurry uniformly stirred in step (1) by a sand mill until the fineness reaches less than 10 μm, and stirring for 40 minutes to obtain a first mixture.

[0277] (3) The remaining 2 / 3 of the polymer fluorosilicone resin, the nano anti-corrosion material and the polyamide wax anti-settling agent are mixed evenly and stirred for 40 minutes to obtain a second mixture.

[0278] (4) The first mixture prepared in step (2) and the second mixture prepared in step (3) are mixed, a polysiloxane defoaming agent is added, and the mixture is stirred for 20 minutes to prepare component A.

[0279] (5) 4-4'-dicyclohexylamine is used as the second component.

[0280] (6) During spraying, mix component A and component B evenly before use.

[0281] The coatings were prepared according to the formulas of the embodiments and comparative examples, and the performance tests were performed:

[0282] The experimental specimens were prepared according to the following construction method, including the following steps:

[0283] (1) The carbon steel substrate is degreased and derusted to at least Sa2.0 level; the construction environment is controlled at a temperature of 10°C to 35°C and a relative humidity of <90%.

[0284] (2) Use airless spraying to spray the paint to the required film thickness in multiple times. After each coat is sprayed and the surface is dry, the next coat can be sprayed.

[0285] (3) The total wet film thickness of the coating is controlled to be 1-2 mm, and the total dry film thickness of the coating is controlled to be 0.5-1 mm. After spraying, the coating is dried at room temperature for 7-15 days to obtain a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating.

[0286] The experimental samples prepared in Examples 1-4 and Comparative Examples 1-3 were tested to test the pencil hardness, bonding strength, tensile strength, wear resistance, temperature resistance, 20% sulfuric acid immersion, 20% sodium hydroxide immersion, and 5% sodium chloride salt spray tests of the coatings. The specific results are shown in Table 1.

[0287] Table 1 Performance results of experimental samples From the test data in Table 1, it can be found that the coating provided by the present invention has excellent hardness, bonding strength, tensile strength, wear resistance, temperature resistance and corrosion resistance. Specifically, through the selection of coating composition and ratio, especially through the combination of fluorine-modified silicone resin, nano-anticorrosive material, wear-resistant powder and functional anti-rust pigment, the corrosion resistance and wear resistance of the coating are significantly enhanced, and it can be applied to complex environments of high temperature, wear and corrosion.

[0288] From the experimental data in Table 1, it can be found that Example 2 uses less resin and more powder to increase the pigment-to-base ratio of the coating, resulting in a certain decrease in the bonding strength and tensile strength compared to Example 1. This shows that the pigment-to-base ratio plays a very important role in the bonding strength and tensile strength of the coating, and the amount of pigments and fillers added should not be too much.

[0289] Example 3 uses a single and low-cost nano-anticorrosion material, wear-resistant powder and functional anti-rust pigment, which results in a significant decrease in wear resistance and a slight whitening of corrosion resistance compared to Example 1, indicating that the combination of various powders plays a very important role in wear resistance and corrosion resistance and is indispensable.

[0290] The silane coupling agent selected in Example 4 is N-(β-aminoethyl-γ-aminopropyl)methylsilane, which has a faster drying speed and cross-linking density, resulting in a significant improvement in pencil hardness and wear resistance compared to Example 1, indicating that the use of a better silane coupling agent can improve the overall cross-linking density of the coating.

[0291] After the molecular weight was changed in Example 5, Example 6, Example 7 and Example 8, the coating performance was not much different, indicating that in the synthesis process of fluorosilicone resin, the molecular weight was controlled between 8000-12000 to meet the quality and performance requirements.

[0292] Comparative Example 1 uses a fluorosilicone resin with a molecular weight of 5000. The hardness of the coating increases, but the bonding strength, tensile strength and wear resistance all decrease significantly, indicating that a too small molecular weight will lead to a decrease in the overall density of the coating.

[0293] In Comparative Example 2, a fluorosilicone resin with a molecular weight of 20,000 was selected. The hardness of the coating decreased significantly, and the bonding strength also decreased accordingly, but the tensile strength increased. The coating as a whole had defects such as slow drying and insufficient cross-linking, which made the coating structure softer and the chemical resistance decreased significantly. This indicates that a too large molecular weight will lead to insufficient cross-linking strength of the coating, decreased hardness, and poor performance.

[0294] In Comparative Example 3, 4-4'-dicyclohexylamine was used alone as the curing agent component, and the hardness, bonding strength, tensile strength and wear resistance all showed a significant decrease, indicating that incomplete drying at room temperature would occur if a silane coupling agent was not added, and the addition of a silane coupling agent was essential.

[0295] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0296] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating, characterized in that: It is made of the following components in parts by mass: 80 to 100 parts of fluorosilicone resin, 10 to 15 parts of nano anticorrosive materials, 5 to 15 parts of wear-resistant powder, 5 to 10 parts of antirust pigment, 1 to 2 parts of siloxane dispersant, 1 to 2 parts of polysiloxane defoamer, 1 to 2 parts of organosilicon leveling agent, 1 to 3 parts of polyamide wax anti-settling aid, 25 to 35 parts of amino curing agent, and 2 to 5 parts of aminosilane coupling agent; Fluorosilicone resin is a fluorosilicone resin with a molecular weight of 8000 to 12000 and containing silicon-oxygen bonds.

2. A high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating according to claim 1, characterized in that: The preparation method of fluorosilicone resin comprises the following steps: Under an inert atmosphere, trifluoropropylmethylcyclotrisiloxane is added to a hydrochloric acid solution, and a first ring-opening polymerization reaction is carried out at 80° C. to 100° C. to obtain a trifluoropropylmethylchloroazane polymer; In an inert atmosphere, a trifluoropropylmethylchloroazane polymer and a tetramethyltetravinylcyclotetrasiloxane are mixed and preheated at 80°C to 100°C for dehydration, and then a catalyst and a neutralizer are added to cause a second ring-opening polymerization reaction at 150°C to 160°C to generate an interpenetrating network fluorosilicone resin, and then the temperature is lowered to 80°C to 90°C for heat preservation and reaction, and then cooled to room temperature to prepare a fluorosilicone resin.

3. A high temperature resistant and heavy corrosion resistant fluorine silicon polymer coating according to claim 2, characterized in that: The molar ratio of trifluoropropylmethylcyclotrisiloxane to the hydrochloric acid solution is 100:2-3; and the reaction time of the first ring-opening polymerization reaction is 1h-2h.

4. A high temperature resistant and heavy corrosion resistant fluorine silicon polymer coating according to claim 2, characterized in that: The molar ratio of trifluoropropylmethylchloroazane polymer to tetramethyltetravinylcyclotetrasiloxane is 2:1-1.5; and the reaction time of the second ring-opening polymerization reaction is 2h-3h.

5. The high temperature resistant and heavy corrosion resistant fluorine-silicon polymer coating according to claim 1, characterized in that: The added amount of the catalyst is 0.3% to 0.4% of the total mass of the trifluoropropylmethylchloroazane polymer and the tetramethyltetravinylcyclotetrasiloxane.

6. The high temperature resistant and heavy corrosion resistant fluorine silicon polymer coating according to claim 1, characterized in that: The added amount of the neutralizer is 0.5% to 0.6% of the total mass of the trifluoropropylmethylchloroazane polymer and the tetramethyltetravinylcyclotetrasiloxane.

7. The high temperature resistant and heavy corrosion resistant fluorine silicon polymer coating according to claim 1, characterized in that: The catalyst is a manganese catalyst; the neutralizer is AMP95.

8. The high temperature resistant and heavy corrosion resistant fluorine silicon polymer coating according to claim 1, characterized in that: The nano anti-corrosion material is one or more of nano alumina, nano iron oxide, nano magnesium oxide, nano titanium dioxide and nano silica gel; The wear-resistant powder is one or more of silicon carbide, wollastonite, zirconium oxide, white corundum and glass powder; The anti-rust pigment is one or more of zinc phosphate, aluminum tripolyphosphate, mica powder and iron oxide.

9. A method for preparing the high temperature resistant and heavy corrosion resistant fluorine silicon polymer coating according to any one of claims 1 to 8, characterized in that: Follow these steps to prepare: Weigh the following components in parts by mass: 80 to 100 parts of fluorosilicone resin, 10 to 15 parts of nano-anticorrosive materials, 5 to 15 parts of wear-resistant powders, 5 to 10 parts of antirust pigments, 1 to 2 parts of siloxane dispersants, 1 to 2 parts of polysiloxane defoamers, 1 to 2 parts of organosilicon leveling agents, 1 to 3 parts of polyamide wax anti-settling aids, 25 to 35 parts of amino curing agents, and 2 to 5 parts of aminosilane coupling agents; 1 / 3 to 1 / 2 of the fluorosilicone resin, the organosilicon leveling agent, the siloxane dispersant, the wear-resistant powder and the anti-rust pigment are mixed evenly, ground, and then the remaining fluorosilicone resin is added and mixed evenly to obtain a first mixture; The remaining fluorosilicone resin, nano anti-corrosion material and polyamide wax anti-settling aid are mixed evenly to obtain a second mixture; After mixing the first mixture and the second mixture, adding a polysiloxane defoamer, and stirring evenly to obtain component A; Mixing an amino curing agent and an aminosilane coupling agent to obtain a component B; During spraying, component A and component B are stirred evenly to obtain a high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating.

10. Use of the high temperature resistant and heavy corrosion resistant fluorosilicone polymer coating according to any one of claims 1 to 8 in the preparation of anti-corrosion materials, characterized in that: The following steps are involved: After the substrate is degreased and derusted, the high-temperature resistant and heavy-duty anti-corrosion fluorosilicone polymer coating is sprayed on the surface of the substrate, the total wet film thickness of the coating is controlled to be 1mm to 2mm, and the total dry film thickness of the coating is 0.5mm to 1mm. After spraying, it is dried at room temperature for 7 to 15 days to prepare a high-temperature resistant and heavy-duty anti-corrosion fluorosilicone polymer coating.

Citation Information

Patent Citations

  • Labor-saving type anticorrosive coating and preparation method thereof

    CN103627317A

  • Organic-inorganic modified high-temperature-resistant anticorrosive wear-resistant coating

    CN109705729A

  • Composite material and preparation method thereof, wear-resistant anticorrosive coating and application

    CN111849351A

  • Coating composition, coating, preparation method and application of coating, and coating layer

    CN113292925A

  • Preparation method of wide-temperature-range solvent-resistant fluorosilicone rubber and composition thereof

    CN114381001A

Cited By

  • Modified fluorosilicone resin coating material with low thermal conductivity and high toughness as well as preparation method and application of modified fluorosilicone resin coating material

    CN120888236A

  • Moisture-curing quick-drying HFG weather-resistant insulating coating as well as preparation method and application thereof

    CN121471814A

  • A moisture-cured quick-drying HFG weather-resistant insulating coating, a preparation method and application thereof

    CN121471814B